Vertebral Artery Dissection Masquerading as Concussion in an Adolescent. Issue 5 (May 2018) - Kumar, Gogi; Ludwig, Bryan; Patel, Vipul V.
Abstract : Objective: Educate providers about the clinical presentation and consequences of delaying diagnosis of traumatic vertebral artery dissection with thromboembolic ischemic strokes in the pediatric population. Vertebral artery dissection is often difficult to diagnose and can be a potentially devastating cause of ischemic stroke. Methods: Review of the chart, peer review/discussion, and imaging interpretation. Results: A 16-year-old boy was admitted with confusion after a head and neck trauma was sustained while wrestling. (Glasgow Coma Scale=15, NIHSS = 0). Investigations including computed tomography (CT) head and cervical spine were normal. He then developed severe nausea, vomiting, dizziness, and headaches and was admitted for symptoms of concussion. Ten hours later, patient declined (hypertensive and unresponsive) and was noted to have decerebrate posturing. After emergent intubation, he was transferred to the pediatric intensive care unit. Repeat CT head showed an acute left cerebellar infarct with associated cerebellar edema resulting in effacement of the fourth ventricle/basilar cisterns and acute hydrocephalus. The CT angiography and magnetic resonance imaging of brain confirmed arterial dissection and near occlusion of the left vertebral artery at the C2 level. Extensive infarct was seen in the left cerebellum, brainstem, and right cerebellum. During a prolonged hospital stay, the family opted to continue care, and he was transferred to an inpatient rehabilitation facility because of limited brainstem activity, being nonverbal, and not demonstrating purposeful spontaneous movements. Conclusions: Detailed history and thorough neurological examination in conjunction with appropriate imaging are necessary to distinguish between brainstem/cerebellar ischemia from vertebral artery dissection and concussion.